2019
DOI: 10.5812/ans.91831
|View full text |Cite
|
Sign up to set email alerts
|

The Urgent Need for Molecular Imaging to Confirm Target Engagement for Clinical Trials of Fragile X Syndrome and Other Subtypes of Autism Spectrum Disorder

Abstract: Promising therapeutic agents for the symptoms in animal models of fragile X syndrome (FXS) have not resulted in similar advances in clinical trials of humans with FXS due to the dearth of tools to quantify their key cognitive and behavioral outcome measures with optimal validity and reliability. Therefore, experts strongly recommended an effort to develop and implement use of biomarkers in unfolding clinical trials in FXS. Molecular imaging provides a spectrum of agents to serve as biomarkers to confirm that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Importantly, this difference in BP ND between the subjects with FXS and control group was significant in areas consistent with known distribution of mGluR5, and which have been functionally implicated in FXS symptomatology. Our results of overall reduced mGlu5 receptor expression in relevant regions of the brain in individuals with FXS replicate recent findings 17 and advance ongoing efforts for a much-needed measure of mGluR5 target engagement for drugs and treatment of symptoms in clinical trials of FXS and related disorders 36 , 37 .…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, this difference in BP ND between the subjects with FXS and control group was significant in areas consistent with known distribution of mGluR5, and which have been functionally implicated in FXS symptomatology. Our results of overall reduced mGlu5 receptor expression in relevant regions of the brain in individuals with FXS replicate recent findings 17 and advance ongoing efforts for a much-needed measure of mGluR5 target engagement for drugs and treatment of symptoms in clinical trials of FXS and related disorders 36 , 37 .…”
Section: Discussionsupporting
confidence: 84%
“…[ 18 F]FPEB 3-[ 18 F]fluoro-5-(2-pyridinylethynyl)benzonitrile ([ 18 F]FPEB), a novel, specific mGluR5 ligand to quantitatively measure the density and distribution of mGluR5s in the brain regions of humans with FXS through PET [21][22][23][24][25][26][27][28][29][30] (Figure 1), constitutes an effective tool to confirm target engagement of mGluR5s of relevance to clinical trials of NAMs for individuals with FXS [31]. Specifically, [ 18 F]FPEB [22,[34][35][36][37] has been shown to demonstrate high uptake and specific binding during the test-retest paradigm for mGluR5 in the anterior cingulate gyrus, putamen, caudate nucleus, and frontal, parietal, and temporal cortices [28,29].…”
Section: Measurement Of Mglur 5 S In the Living Human Brainmentioning
confidence: 99%
“…Our finding that mGluR5 expression measured by positron emission tomography (PET) with 3-[ 18 F]fluoro-5-(2-pyridinylethynyl)benzonitrile ([ 18 F]FPEB), a potent and safe specific mGluR5 inhibitor (Figure 1 and Figure 2) [58,59], is reduced in all brain regions in men with FXS [2] compared to participants of both sexes with ASD and TD [2,42,[60][61][62], was confirmed utilizing positron emission tomography and magnetic resonance (PET/MR) imaging on an unmedicated cohort of older men with FXS and age-and sex-matched participants with TD suggesting that the current protocol may be a valuable biomarker for mGluR5 expression in clinical trials of novel agents for humans with FXS and other subtypes of ASD [63]. We showed that [ 18 F]FPEB may be a promising tool to obtain quantitative measurements of mGluR5 expression in individuals with FXS for clinical trials and other investigations [2,42,[64][65][66][67]. Since our prior finding of reduced cerebral mGluR5 expression in cortical and subcortical regions of men with FXS has been confirmed [41,63], we sought expand the previous protocol of cerebral mGluR5 expression alone with a more refined measure tool to include simultaneous FRMP levels and cerebral mGluR5 expression for clinical trials of FXS.…”
Section: Introductionmentioning
confidence: 88%
“…The protocols for the study of humans were approved by the Institutional Review Boards of the Institute for Neurodegenerative Disorders (IND) in New Haven, Connecticut [74] and the Johns Hopkins University (JHU) in Baltimore, Maryland [75,76]. Since exposure to radioactivity in PET constitutes greater than minimal risk, this pilot [41,42,64,[71][72][73]. We aimed to determine if (A) FMRP levels are correlated with mGluR 5 expression in men with the FM of FXS [2,41,42] and (B) the measurement of FMRP and PET with ([ 18 F]FPEB) is feasible in men with FXS [2,41,42,60,61].…”
Section: Recruiting Sitesmentioning
confidence: 99%
See 1 more Smart Citation